The Influence of Price, Brand Image, and Product Quality on Purchasing Intention in Indomie Consumers in The City of Surabaya - Putri, Helvy Novia (JEMBA: Journal of Economics, Management, Business and Accounting, 2023)
This research is focused primarily on the relationship between price, brand image, and product quality and purchase intention "The Effect of Price, Brand Image, and Product Quality on Purchase Intention in Indomie Consumers in Surabaya City". The main point that is the background for this problem to be discussed is Indomie, which is the top leader in the sale of packaged instant noodles in Indonesia. This happens because of the high consumer buying intention in these products. To be able to attract and increase consumer buying intention, there are various factors that influence, including price, brand image, and the quality of the product itself. The objectives of this study are to: 1) determine the significant relationship between price and purchase intention of Indomie consumers in Surabaya; 2) determine the significant relationship between brand image and purchase intention of Indomie consumers in Surabaya city; 3) determine the significant relationship between product quality and purchase intention of Indomie consumers in Surabaya city; and 4) ensure a significant relationship between price, brand image, and product quality simultaneously. The sample applied in this study was 100 respondents with predetermined criteria. This research applies quantitative methods with multiple regression analysis techniques, and data analysis tools apply SPSS version 22.0 and Microsoft Excel 2007. The conclusion of this study is that there is a significant partial and simultaneous influence between price, brand image, and product quality on buying intention in Indomie consumers in Surabaya city.